Role and influence of rubric-referenced assessment in postgraduate education: a case study from a Malaysian public university - Luan, Wong Su; Jing, Teh Liang; Hong, Tang Sai; O. K Rahmat, Rahmita Wirza.; Md. Khambari, Mas Nida (South East Asia Association for Institutional Research, 2024)
Rubric-referenced assessments have been postulated to have both benefits and drawbacks on student learning outcomes. The ambiguity regarding the influence of rubrics on Malaysian postgraduate students' learning experience persists. Thus, in this study, a case study qualitative approach was adopted to explore postgraduate students’ perception towards the role and influence of assessment rubrics in their learning experience. Criterion purposeful sampling was employed to select five postgraduate students and the Activity Theory was adopted as the theoretical foundation of the study. Data were collected via focus group discussion and were analysed using content analysis. The findings revealed that the explicit criteria in rubrics provided postgraduate students with clarity on the instructor’s expectations, enabling them to set specific academic goals and approach their tasks purposefully. This eventually reduced their anxiety and increased their motivation and confidence in completing the assignments. Nevertheless, one student expressed that the preset criteria could limit learner’s creativity and voice. The study also found that students perceived rubrics to have a positive influence on their learning strategies and knowledge gained. The students used rubrics as a tool to facilitate academic goal setting and self-assess their learning progress. Consequently, their knowledge retention and academic achievement improved. The findings imply that rubric-reference assessments should be contemplated by tertiary-level educational stakeholders. However, a well-designed rubric needs to be followed by sound implementation. Ongoing communication is key both between the instructors and between instructors and students to develop a shared understanding of the rubric.